Serine Integrase attP Binding and Specificity. Issue 21 (19th October 2018) - Li, Huiguang; Sharp, Robert; Rutherford, Karen; Gupta, Kushol; Van Duyne, Gregory D.
Abstract: Serine integrases catalyze the site-specific insertion of viral DNA into a host's genome. The minimal requirements and irreversible nature of this integration reaction have led to the use of serine integrases in applications ranging from bacterial memory storage devices to gene therapy. Our understanding of how the integrase proteins recognize the viral ( att P) and host ( att B) attachment sites is limited, with structural data available for only a Listeria integrase C-terminal domain (CTD) bound to an att P half-site. Here we report quantitative binding and saturation mutagenesis analyses for the Listeria innocua prophage att P site and a new 2.8-Å crystal structure of the CTD att P half site. We find that Int binds with high affinity to att P (6.9 nM), but the Int CTD binds to att P half-sites with only 7- to 10-fold lower affinity, supporting the idea that free energy is expended to open an Int dimer for att P binding. Despite the 50-bp Int– att P interaction surface, only 20 residues are sensitive to mutagenesis, and of these, only 6 require a specific residue for efficient Int binding and integration activity. One of the integrase DNA-binding domains, the recombinase domain, appears to be primarily non-specific. Several substitutions result in an improved att P site, indicating that higher-efficiency attachment sites can be obtained through site engineering. These findings advance our understanding of serine integrase function and provide important data for efforts towards engineering this family of enzymes for a variety of biotechnology applications. Graphical abstract: Highlights: Serine integrases are important tools in biotechnology. Listeria innocua Int binds to the att P site with K d  = 7 nM. Only 20 of the 50 att P residues are sensitive to substitution. Specificity is provided by the zinc ribbon and linker regions of Int. This work will facilitate improvement of serine integrase systems.